Association between blood hemoglobin levels, anemia, and body mass index in children and women of Myanmar: findings from a nationally representative health study - Shiva Raj Acharya; Diwash Timilsina; Sabitri Acharya (Scientific Reports)
Abstract Despite the high prevalence of anemia and malnutrition in Myanmar, the relationship between anemia and body mass index (BMI) remains underexplored. We analyzed nationally representative data from the Myanmar Demographic and Health Survey (MDHS) 2015–2016 to explore the effects of BMI on hemoglobin levels and anemia among children (n = 2,937) and women (n = 9,262). Anemia was defined as hemoglobin levels < 11 g/dl for children and pregnant women, and < 12 g/dl for nonpregnant women, with BMI categories classified according to WHO guidelines. General linear models, Pearson’s correlation, and logistic regression models were used in the analysis. Mean blood hemoglobin levels were 10.69 ± 1.30 g/dl for children and 11.96 ± 1.56 g/dl for women. Increased BMI was associated with increased hemoglobin levels in women (R = 0.142, p < 0.001). Logistic regression models predicted that severely underweight (COR, 1.26; CI: 1.02–1.57) and underweight women (COR, 1.17; CI: 1.02–1.34), pregnant women (AOR, 6.85; CI: 5.20–9.02), women with poorest wealth index (COR, 1.16; CI: 1.02–1.33), and women from rural regions (AOR, 1.13; CI: 1.01–1.26) and coastal zones (AOR, 1.65; CI: 1.40–1.95) were at higher risk of anemia. This study demonstrates a positive association between BMI and blood hemoglobin levels, with a lower risk of anemia in overweight and obese women. However, no associations were observed in children. Targeted nutritional interventions for underweight and pregnant women might be beneficial in mitigating anemia risk.